2005
DOI: 10.1161/01.res.0000156274.72390.2c
|View full text |Cite
|
Sign up to set email alerts
|

Induced Deletion of the N-Cadherin Gene in the Heart Leads to Dissolution of the Intercalated Disc Structure

Abstract: The structural integrity of the heart is maintained by the end-to-end connection between the myocytes called the intercalated disc. The intercalated disc contains different junctional complexes that enable the myocardium to function as a syncytium. One of the junctional complexes, the zonula adherens or adherens junction, consists of the cell adhesion molecule, N-cadherin, which mediates strong homophilic cell-cell adhesion via linkage to the actin cytoskeleton. To determine the function of N-cadherin in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
298
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 298 publications
(321 citation statements)
references
References 43 publications
15
298
1
3
Order By: Relevance
“…We previously demonstrated that cardiac-specific deletion of N-cadherin resulted in downregulation of Cx43-containing gap junctions and sudden arrhythmic death in mice (15,16). Based on the severity of this phenotype, we speculated that gap junctions might be affected in animals expressing half the normal levels of N-cadherin thus leading to an intermediate phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that cardiac-specific deletion of N-cadherin resulted in downregulation of Cx43-containing gap junctions and sudden arrhythmic death in mice (15,16). Based on the severity of this phenotype, we speculated that gap junctions might be affected in animals expressing half the normal levels of N-cadherin thus leading to an intermediate phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…The N-cadherin mutant allele lacking exon 1 was generated as previously described (15). The N-cadherin and Cx43 heterozygous mice were intercrossed and genotypes determined by polymerase chain reaction (PCR).…”
Section: Generation Of Compound Heterozygous Micementioning
confidence: 99%
See 1 more Smart Citation
“…It is also this inner layer of cardiomyocytes that detectably sends cell processes, as well as secretes proteins, into the subjacent cardiac jelly layer. Additionally, a member of a the Caϩϩ-dependent family of adhesion molecules, N-cadherin, is responsible for the connection of actin and myofibrils between neighboring myocytes at cell-cell junctions (Linask, 1992a;Kostetskii et al, 2005) and for the cell alignment and arrangement of the two layers of the developing heart tube (Shiraishi et al, 1993). Thus, during looping, as in the earlier period of cardiac compartment formation, cross-talk between two adhesion mediated-signaling pathways, integrin and N-cadherin, is evident (Linask and Lash, 1990;Linask, 1992b;Linask et al, 2005b) and as shown here, appears to be facilitated by the actinnonmuscle myosin-II complex.…”
Section: Actomyosin Cytoskeleton and Heart Loopingmentioning
confidence: 99%
“…To overcome embryonic lethality, a Cre/lox conditional knockout was generated to examine the role of N-cadherin after development of the myocardium was complete [109]. It was noted that a knockout of the N-cadherin gene also resulted in loss of α-, β-and γ-catenin, as well as desmoplakin and p120.…”
Section: Changes In Expression Of Intercalated Disc Proteins and Theimentioning
confidence: 99%